Understanding the Relationship Between Islam and Fundamentalism in the Qur'an: Memahami Hubungan Antara Islam dan Fundamentalisme dalam Al-Qur’an - Dyaaz Muhammad; Eka Nurkamilah; fina Rahma indira (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
The human being was created by God as a social creature in whose mutual need belongs to the multiplicity of needs. Islam as the religion we admire has some principles of life in it that we ourselves cannot follow. of course, times and the speed of technology of course this has an impact on all the sciences of Islam except because it can facilitate us ourselves of course because the dissemination of information obtained by one source can be rapid and can be directly spread to another as additional information. Fundamental is something of a fundamental nature. Islam and fundamentalism are beliefs or desires to preserve integrity and uphold existing religious norms. But with this, people don't necessarily know for sure and understand what fundamentalism itself means. In religion too, of course, this fundamentalism is used either from Islam, Christianity, Hinduism, Buddhism, or any other religion. This is because the beliefs and firmness of its creators are correctly considered either small or large. In this case, fundamentalism becomes the foundation of the religion. However, when one has reached this level, it should be noted also not to come later when there is a difference one thing in religion it will be a dispute.